2018
DOI: 10.1016/j.bios.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated tripodal receptors for potentiometric chloride detection in biological fluids

Abstract: Fluorinated tripodal compounds were recently reported to be efficient transmembrane transporters for a series of inorganic anions. In particular, this class of receptors has been shown to be suitable for the effective complexation of chloride, nitrate, bicarbonate and sulfate anions via hydrogen bonding. The potentiometric properties of urea and thiourea-based fluorinated tripodal receptors are explored here for the first time, in light of the need for reliable sensors for chloride monitoring in undiluted biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The chloride bindingp roperties of these compounds has been previously reported, [16] however developmentsi nb inding isotherm fitting methodology now allows more complex equilibria to be analysed. [17] The compounds were found to bind chloride with stepwise higher stoichiometry, [18] and the curve-fitting analysiso ft he binding isotherms for compounds 1-10 gave abetter fit to the 1:2receptor:anion bindingm odel than the 1:1m odel. The associationc onstants (K a )o btained (Table 1) show thiourea compounds 6-10 bind chloride with ah igher affinity compared to the analogousu rea compounds 1-5.This has been observedp reviously,and is presumably due to the more acidic nature of the thiourea hydrogen bond donor.…”
Section: Resultsmentioning
confidence: 99%
“…The chloride bindingp roperties of these compounds has been previously reported, [16] however developmentsi nb inding isotherm fitting methodology now allows more complex equilibria to be analysed. [17] The compounds were found to bind chloride with stepwise higher stoichiometry, [18] and the curve-fitting analysiso ft he binding isotherms for compounds 1-10 gave abetter fit to the 1:2receptor:anion bindingm odel than the 1:1m odel. The associationc onstants (K a )o btained (Table 1) show thiourea compounds 6-10 bind chloride with ah igher affinity compared to the analogousu rea compounds 1-5.This has been observedp reviously,and is presumably due to the more acidic nature of the thiourea hydrogen bond donor.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 3 based membrane had linear response toward chloride ion from 10 −5 to 10 −1 M with slope of 55 mV/decade. The sensor exhibited fast response time and superior selectivity to previous reported chloride ionophores .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of selective chloride ionophores for samples that contain salicylate or thiocyanate as in the case of blood or serum samples no suitable ISEs available for chloride measurement [34]. Although it had been reported that the ion selective membranes with tren-based tris-urea bis(CF 3 ) tripodal compound exhibited the selectivity for chloride over salicylate and thiocyanate, the interfering anions are still preferred at the same concentration level with logK Cl À , Sal À (pot) = + 1.0 [34]. In this work the tripodal squaramide derivatives with different phenyl substitutes 1-3 were incorporated into plasticized PVC membranes with TDMACl as ion exchangers.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the interfering ion is effectively removed from the membrane surface by diffusion into the membrane bulk. The effect is most useful with membranes that contain a high ion‐exchanger salt concentration and that exhibit a relatively high ion mobility . For relatively short contact times a reduced level of interference is observed, seemingly in defiance of the ion‐exchange equilibrium.…”
Section: Introductionmentioning
confidence: 99%